PENERAPAN METODE EXPERIENTAL LEARNING DALAM PEMBELAJARAN MENULIS TEKS PUISI PADA SISWA KELAS X SMA NEGERI I TUKDANA TAHUN 2023/2024 - Sholeh, Muhammad; Apriyanto, Ade; Mutmainnah, Zahrotul (Transpublika Publisher, 2024)
The Experiential Learning method is one method learning that can be done make the learning process effective teaching on the material write text poetry. Based on results observation, can concluded that learning write text poetry Still experience a number of constraints, ie student not enough enthusiastic in follow learning, even deep _ learning write poetry. Student not enough creative for find ideas within write poetry and the methods used in learning Still use method conventional, so student fast feel saturation is what causes it delivery material provided by the teacher is lacking understood by students. Study This is study quantitative, i.e experiment pseudo with nonequivalent control group design. The results of statistical test calculations are obtained mark T count 7,678> T table 1,668 with df 66, respectively second class the obtained P value = 0.00 ˂ 0.05. From the results of these statistical tests, method experiential learning stated effective in learning write text poetry to students class X SMA 1 Tukdana Year Teachings 2023/2024